(untitled) (Advancements in Homeopathic Research, 2023)
Introduction: Constipation is a prevalent gastrointestinal condition globally, often managed with conventional laxatives that may cause side effects and dependency. Homeopathy, offering a holistic approach through diluted natural substances, aims to stimulate the body’s self-healing mechanism. This study evaluates Good Morning™ drops, an innovative homeopathic formulation designed to safely and effectively manage constipation. Using a rat model of Loperamide-induced constipation, we evaluated its safety and efficacy, unveiling promising results.Materials and Methods: A rat model of Loperamide induced constipation was utilized to assess the efficacy and safety of Good Morning™ Constipation Drops. 3 unique formulations were prepared and employed to the animal model in 3 different doses. 72 rats were randomly assigned to 12 groups (3 control groups plus 3 formulations in 3 different doses totalling 9 groups), receiving specific variants or control treatments over the period of 21 days. Parameters including body weight, water intake, stool count, intestinal function, haematology, bleeding and clotting time, blood biochemistry, and organ weight were evaluated. Results and discussion: The results showed that all homeopathic formulations, particularly Variant 2, exhibited significant effects in Loperamide induced constipated rats. Across various parameters, Variant 2 consistently influenced food intake, stool characteristics, and small intestine motility. Safety assessments indicated overall well-being, withVariant 2 demonstrating superior survival outcomes. These findings position Variant 2 as a promising candidate for constipation management, emphasizing its consistent efficacy and safety in the rat model. Conclusion: In conclusion, Good Morning™ Constipation Drops exhibited a promising blend of safety, efficacy, and a multifaceted mechanism of action. The formulation, rich in botanical ingredients, demonstrates high safety with favorable survival rates. Efficacy is evident in improved stool counts, stool weights, Small Intestine Transition percentages, and impacts on lipid profiles and liver enzymes, highlighting its potential as a comprehensive solution for constipation relief.